Pergeseran Tradisi Khitan Anak Perempuan di Kudus Jawa Tengah - Moh Rosyid (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This paper aims to describe the shift in the circumcision tradition of girls in Kudus, Central Java. The focus of this shift discussion was mainly on the shift of circumcision done by Dukun Bayi (Traditional Midwife) to that done by a professional midwife, and the prevailing cultural shift is also illustrated. The data were collected through interviews with mothers of the circumcised girls through random sampling. This research is categorized as a case study. The collected data were analyzed using a qualitative descriptive approach. The results of the study revealed that the tradition of girl circumcision is a result of following a tradition that has been done for ages, the understanding of fiqh experts plays a role in the circumcision of girls. As the village midwife is serving childbirth, the circumcision that was initially done by a dukun now is done by professional midwives. The dukun played as a massage therapist to mothers with old pregnancy, also to the postpartum mothers and their babies. The knowledge that girls circumcision needs to be done by medical staff (midwives) will be more optimal if the village government facilitates the role of village midwives in Kudus. Tulisan ini bertujuan untuk mendeskripsikan pergeseran tradisi khitan anak perempuan di Kudus, Jawa Tengah. Faktor utama perubahan tersebut adalah munculnya pengkhitan bidan desa—yang sebelumnya dilakukan oleh dukun bayi—dan menggambarkan perubahan budayanya. Data diperoleh melalui wawancara dengan ibu dari anak perempuan yang dikhitan secara random sampling. Riset ini kategori studi kasus, data yang terkumpul dianalisis dengan pendekatan deskriptif kualitatif. Hasil penelitian mengungkapkan bahwa tertradisinya mengkhitan akibat mengikuti tradisi, yakni pemahaman ahli fikih tentang khitan pada anak perempuan. Seiring adanya bidan desa yang melayani persalinan warga, maka pengkhitan yang semula dukun bayi ada yang dialihkan pada bidan desa. Dukun bayi diperankan sebagai tukang pijet pada ibu yang usia kandungannya menua dan memijat ibu pascamelahirkan beserta bayinya. Hal yang perlu dipahami agar mengkhitan anak perempuan dilakukan oleh tenaga medis (bidan) makin optimal bila peran bidan desa difasilitasi oleh pemerintah desa di Kudus.